Cachaça fermentation biomass as an ingredient in oregano sticks. Issue 2 (9th February 2022) - Lima, Pâmela Cristina; Biz, Ana Paula; Bertolo, Angélica Patrícia; Bagatini, Lucíola; Rigo, Elisandra; Cavalheiro, Darlene
Abstract: Background: Waste from the production of cachaça is often discarded. However, studies report that fermentation yeasts and their derivatives have high protein content, and they are rich in minerals and B‐complex vitamins. Also, research has been shown that the addition of the spent yeast to food leads to a significant increase in nutritional value. In this context, the present study aimed to investigate the use of yeast biomass from cachaça production in snack food. Results: Physical–chemical characterization of yeast biomass confirmed that cell autolysis significantly changed the chemical composition and color of the samples. Concerning the oregano sticks, the addition of natural biomass and autolyzed biomass also significantly modified the proximate composition. Moreover, the acceptability test showed that the addition of autolyzed biomass as an ingredient in the stick formulation obtained the highest acceptance index by the panelists. Conclusion: The addition of 10% yeast biomass from cachaça in the formulation of oregano sticks led to an increase of 14% on the protein content. Besides, the use of yeast biomass also presented a good acceptance by the panelists during sensorial analysis. Therefore, this work found that the addition of yeast biomass from cachaça fermentation process has the potential to be used as an ingredient in food formulation.